Barriers to conducting implementation science research in Asia: An online survey - Wen Ting Tong; Chor Yau Ooi; Yee En Lim (PLoS ONE, 2025)
Background Implementation science (IS) has importance in Asia to facilitate effective delivery of evidence-based interventions to bridge disease prevention and management gaps. However, IS research conducted in Asia are slower compared to the Western region. Purpose This study aims to assess barriers to conducting IS research in Asia. Methods This study adopted a cross-sectional online survey design. Researchers who had conducted IS research in Asian settings completed a questionnaire which examined socio-demographic characteristics, IS research practices, and yes or no items on the various barriers to conducting IS research. An open-ended question was provided to gather additional barriers. Results The response rate for this study was 40.1% (113/282). More than half of the participants has PhD level education (68.1%, n = 77), and 46.0% (n = 52) were academic lecturers. The most common barrier to conducting IS research was the lack of funding (86.7%, n = 98) followed by the lack of awareness (59.5%, n = 67), the lack of time (56.6%, n = 64), and the lack of organisational support (48.7%, n = 55). The open-ended responses elicited additional barriers: the lack of commitment and involvement from stakeholders other than researchers, perceived low value of IS research, the lack of scientific rigour as a field, existing knowledge, system and practices challenge, the lack of capacity or training support, and the lack of academic progression indicators. Conclusions To facilitate the increase of IS research in Asia, more support are needed in terms of availability of funding, capacity building and training in the region, and effective ways to build constructive long-term collaborations with stakeholders.